ANALISIS VERIFIKASI TEKNIS PENEGASAN DAN PENETAPAN BATAS DESA/KELURAHAN DIKOTA JAYAPURA PROVINSI PAPUA - Sandra, Alex; Zuriyani, Elvi; Rahmat, Firdaus; Belvandi, Fajri (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
To provide legal certainty regarding regional management, village boundaries are determined and confirmed. Based on Minister of Home Affairs Regulation Number 45 of 2016, regional heads form Village Boundary Determination and Confirmation Teams at the district level to determine and establish village boundaries. This is done by determining points and boundary lines and pouring them into the map. Organizing geospatial information includes determining and confirming village boundaries. This produces the basic components of village or sub-district administrative boundaries. Government Regulation Number 45 of 2021 concerning the Implementation of Geospatial Information stipulates that operations related to geospatial information must be coordinated with the Geospatial Information Agency (BIG). Through the Circular Letter of the Director General of Village Government Development, Ministry of Home Affairs Number 1463/3835/BPD dated 30 August 2021, the Ministry of Home Affairs and BIG synchronized the determination and confirmation of village boundaries. Based on the circular, BIG will be technically responsible for the process of determining and confirming village boundaries.